2019
DOI: 10.9775/kvfd.2018.21598
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus acidophilus ve Yeşil Çay Pudrası ile Üretilen Yoğurtların Probiyotik Raf Ömrü, Antioksidan, Duyusal, Fiziksel ve Kimyasal Özellikleri

Abstract: The aim of the present study was to determine the effects of the addition of green tea powder (GTP) in the production of yogurt on survival of Lactobacillus acidophilus (P) and the yogurt properties. Four yogurt groups (yogurt without P and GTP, Control, C; yogurt with P and without GTP, PC; P + 1% GTP; and P + 2% GTP) were produced. The yogurt samples were stored at 4°C. The addition of GTP into milk did not affect the viability of yogurt bacteria during fermentation. The highest count of L. acidophilus was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…Many studies report a decrease in the viability of LABs in yogurts during storage 33‐35 . However, according to the results of our study, it was seen that there was no difference in the viability of LABs between the storage days and there was an increase towards the end of the storage.…”
Section: Resultscontrasting
confidence: 61%
“…Many studies report a decrease in the viability of LABs in yogurts during storage 33‐35 . However, according to the results of our study, it was seen that there was no difference in the viability of LABs between the storage days and there was an increase towards the end of the storage.…”
Section: Resultscontrasting
confidence: 61%
“…Additionally, probiotics stimulate the production of certain antioxidant biomolecules, including exopolysaccharides [ 35 ]. Çakmakçı et al [ 36 ] revealed that yogurt produced with classic culture + Lactobacillus acidophilus had higher antioxidant properties than that of control made using classic culture.…”
Section: Resultsmentioning
confidence: 99%